Cuidados domiciliarios para disminuir síndrome geriátrico caídas en la asociación adulto mayor “Jesucristo Redentor” Cantón Huaca - Cuasquer García, Paola Aracelly (2025)
Elderly people are one of the priority groups with the highest risk of developing diseases, this latter premise is the reason for this study to develop home care strategies to diminish the geriatric symptoms caused by accidental falls in the Association for Elderly People “Jesus Redentor”, located in the canton Huaca. To this purpose a methodology based on the quantitative paradigm was used, supported in research with bibliographic type, descriptive, field and action. The gathering of the information was made by diverse methods such as historic-logic, inductive-deductive, analytic-synthetic and systemic approaches; similarly, the instrument of research was the questionnaire which was applied to the population of this research; the most relevant results showed that 56% of interviewed people are between 70 and 79 years old, 50% claimed to live by themselves which increases their vulnerability to falls due to lack of physical or immediate assistance; in addition, 54% do not have any educational level which represents a limitation regarding their comprehension about preventive measures, likewise 76% do not work which contributes to having a sedentary life thus affecting their muscle strength and balance.; 47% experience this geriatric syndrome quarterly, mainly in their bedroom or living room 49%, while performing simple movements such as walking or getting up 53%, 61% wear supportive shoes although not necessarily adequate. The design of the components for developing home care strategies focused on reducing geriatric syndromes caused by falls, was aimed to address these identified needs, integrating educational strategies, promotion, and prevention.